Estimating the reduction of carbon dioxide (co2) emission from private vehicles in penang island - Razif, Mohammad Zahin Mohammad (Universiti Sains Malaysia, 2019)
The staggering number of vehicles on the road in Penang Island that keeps increasing as the day goes by has its drawbacks. The limited space of the historical island only worsens the situation as the roads suffer from massive traffic jam especially during peak hours. Traffic jam causes greater vehicle emissions to be released on the road. The gases released by vehicles comprise of carbon dioxide (CO2), sulphur dioxide (SO2) and hydrocarbons (HC) among many others. These gases are harmful to the environment and in the long run, it may affect the well-being of the creatures on earth. It also proves to be unsustainable. This study investigates the effect of CO2 emission when private vehicles travelling on the road are reduced. Based on the proposed future Penang LRT alignment, seven locations along the Light Rail Transit (LRT) alignment which are also located on the eastern side of Penang Island were chosen for the study. The seven locations are Bandar Sri Pinang zone (BSPZ), Skycab zone (SKYZ), East Jelutong zone (EJZ), Batu Uban zone (BUSZ), Sungai Nibong zone (STZ), Bukit Jambul zone (BJZ) and Jalan Tengah zone (JTZ). In this study, data were collected by means of traffic count survey using GoPro video recording at all seven locations. The data extracted were analysed and total current carbon dioxide (CO2) emission stood at 1803 kgCO2/PCU. Reduction of private vehicles in PCU by 40%, 50% and 60% shows a directly proportional reduction of total CO2 emission which was 1443 kgCO2/PCU, 1331 kgCO2/PCU and 1254 kgCO2/PCU. The findings in this study could be used as a reference for state government in facilitating state government’s policy towards sustainable growth.